Controversy over the Power Between the Papacy and the Empire in the light of Marsilius’ of Padua Defensor pacis - Białas, Anna (Peitho. Examina Antiqua, 2010)
The most famous medieval controversy over the power and the temporal dominion took place between the papacy and the empire. One of the greatest advocates of the imperial domination was Marsilius of Padua, the author of an original work that demonstrated the advantage of acknowledging the emperor’s superiority over the Pope’s. The Defensor pacis, written between 1319 and 1324, was devoted to the dispute on such sovereignty issues as proving that the Pope should be subordinate to the Emperor, and not vice versa. The Defensor pacis takes issue with numerous arguments and views uttered by the papal camp and uses the appropriate quotations from the Bible and Aristotle to show their weakness and inconsistency. The work comprises three parts. The first part is a description of the ideal system, i.e., an elective monarchy, with the specified role of a ruler and a clear indication of the sovereignty of the people. The second and third parts present a challenge to the arguments of the papal camp (including the famous argument of the “power keys”) and analyze the general situation of the Church, suggesting the necessary reforms. Thus, the whole work becomes a compendium of knowledge on appropriate governance.